Poverty Alleviation and Social Safety Net Schemes for Economies in Transition - Paull, Gillian (IMF Working Papers; Working Paper ;, 1991)
Inspired by the current Polish economic restructuring program, this paper attempts to develop a general income support scheme that could serve as a model to alleviate poverty in developed economies in the transitional phase. The proposed scheme has the advantage that no part of the poor population is omitted from eligibility for support sufficient to remove them from poverty. The concept of the simplified model is protection against poverty through income maintenance that is conditional upon fulfillment of forward-looking requirements such as workfare, training or job search. Further, the scheme considers methods whereby limited national resources can be managed by official policies that combine into a coherent, cost-effective package, an optimal mix of income guarantee levels and incentive effects.